Interaction between the septal area and the subfornical organ in the control of water intake induced by thirst-eliciting procedures - Morita, Norihiro [UNESP]; Saad, W. A. [UNESP]; Camargo, L. A A [UNESP]; Silva Neto, C. R. [UNESP]; Antunes-Rodrigues, J. [UNESP]; Covian, M. R. [UNESP] (Elsevier, 1980)
Rats bearing lesions in the septal area followed by lesions in the subfornical organ were submitted to various thirst-eliciting procedures. The rats with hyperdipsia induced by lesions of the septal area drank more water than either during the control period or after lesion of the subfornical organ under the same thirst-eliciting or angiotensin-liberating stimuli (polyethyleneglycol, isoproterenol, water deprivation and ligation of the inferior vena cava). The overdrinking elicited by lesions in the septal area was blocked after lesion of the subfornical organ. Neither hypovolemia, nor hypotension or water deprivation could elicit increased water intake in animals whose subfornical organ had been destroyed. Animals with lesions in the subfornical organ showed decreased water intake after cellular dehydration. The results obtained suggest that the subfornical organ acts as a more important structure than the septal area in the regulation of water intake elicited by angiotensin, with two opposite effects: a direct one facilitating water intake, and an indirect one inhibiting the septal area. The septal area has an inhibitory effect on the subfornical organ and on water intake. © 1980.
Keywords: Cellular dehydration; Hypotension; Hypovolemia; Septal area; Subfornical organ; Thirst-eliciting procedures; Water intake; Animal experiment; Blood and hemopoietic system; Cardiovascular system; Central nervous system; Fuid intake; Hypotension; Hypovolemia; Rat; Septum pellucidum; Thirst; Animals; Drinking; Isoproterenol; Male; Neurosecretory Systems; Polyethylene Glycols; Rats; Septal Nuclei; Sodium Chloride; Subfornical Organ; Thirst; Vena Cava, Inferior; Water Deprivation